EKSPLORASI MATEMATIKA KUE KHAS MANDAR: KUE BIKANG SEBAGAI SUMBER BELAJAR DI SEKOLAH - Selvia Nur; Wanasari Wanasari; Ronald Kurniawan; Arni Arni; Aprisal Aprisal (Program Studi Pendidikan Matematika, 2024)
Mathematics is often considered a very difficult lesson and a science that is free from cultural influences. However, this forms negative perceptions of students. Most students think that learning mathematics is not related to culture. This may be because the mathematics taught in schools is not contextual and is very far from the reality of students' daily lives. As a unitary country, Indonesia has a variety of cultures. However, many teachers do not yet know that the culture around them can be used as material for learning mathematics. Bikang cake is part of Mandar culture. Without realizing it, making bikang cakes contains mathematical concepts. Therefore, this research aims to apply the manufacturing process involving mathematical concepts. This research is descriptive research with an ethnographic approach. Data collection techniques through observation, interviews and documentation. This research shows that the process of making bikang cakes contains mathematical concepts such as plane shapes, fraction concepts and triangles. Therefore, this research can be used as a contextual mathematics learning resource in schools.